2021
DOI: 10.9734/jpri/2021/v33i58a34128
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacognostical Profile of Gymnema sylvestre and its Anti-Hyperglycemic Activity

Abstract: In this paper explored the pharmacognostical profile of gymnema sylvestre and its anti-hyperglycemic activity has been documented well with references. The importance of the species in Ayurveda has been highlighted. The bioactive components like gymnema sylvestre has a variety of secondary metabolites, including oleanane, gymnemic acid, gymnemasides (A-F), gymnemic acid (IXVIII) homologue, gymnemic acid A1 and its derivatives, triterpenoidsaponin, al has been clearly includedin the review kaloid (Conduritol-A)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…It has been generally expressed that oxidative stress created because of free radicals 13,14 is engaged with the advancement of diabetes by pancreatic cell annihilation. 15,16 Assessed the methanolic leaf extract of GS on glucose transport and insulin resistance in vitro. The result showed that the extract enhanced in L6 myotubes, ameliorating the insulin resistance in 3T3 murine adipocyte cell line in-vitro.…”
Section: Discussionmentioning
confidence: 99%
“…It has been generally expressed that oxidative stress created because of free radicals 13,14 is engaged with the advancement of diabetes by pancreatic cell annihilation. 15,16 Assessed the methanolic leaf extract of GS on glucose transport and insulin resistance in vitro. The result showed that the extract enhanced in L6 myotubes, ameliorating the insulin resistance in 3T3 murine adipocyte cell line in-vitro.…”
Section: Discussionmentioning
confidence: 99%